PENGARUH PEMBERIAN LAYANAN INFORMASI TERHADAP PENINGKATKAN KEPERCAYAAN DIRI SISWA KELAS XI IPA SMA NEGERI 2 PEKANBARU T.A 2014/2015 - Randi Gunola Randi Gunola; Tri Umari Tri Umari; Raja Arlizon Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: this research was purpose to: 1) To knows the level of student’s self-confident before the information service was gave. 2) To knows the level of student’s self-confident after the information service was gave. 3) To knows the different level of student’s self-confident from before than after gave information service. 4) To find out influence of giving information service about raising self-confident at students in class XI IPA stated-owned senior high school 2 Pekanbaru 2014/2015. This research was using pre-experimental methods with one group pre-test and post-test design. The sample are students in class XI IPA was have low self-confident level totally 56 persons. In this research there are 4 times faced to giving information service, start from pre-test questionnaire and stopped by post-test questionnaire. Phenomenological was used is quantitative with research method pre-experimental design with T-test, sample method was taken used simple random sampling. Research instrument was used is questionnaire. Review from this research show that there is positif influence signifficancy from information service was given about raising students self-confident, that is as many as 44,89% with signifficancy level is 0,000<0,05.Key Words: Self-Confident, Student, Information Service